2018
DOI: 10.3390/nano8020067
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Interaction and Tumoral Penetration Properties of Cyclodextrin Nanoparticles on 3D Breast Tumor Model

Abstract: Amphiphilic cyclodextrins are biocompatible oligosaccharides that can be used for drug delivery especially for the delivery of drugs with solubility problems thanks to their unique molecular structures. In this paper, Paclitaxel was used as a model anticancer drug to determine the inclusion complex properties of amphiphilic cyclodextrins with different surface charge. Paclitaxel-loaded cyclodextrin nanoparticles were characterized in terms of mean particle diameter, zeta potential, encapsulation efficacy, drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…The IC 50 value of β-CD:EV was higher than that of EV, suggesting that conjugation significantly affect EV efficacy ( P < 0.01), possibly due to the slow release profile of EV from the inclusion complex. 47,48 Interestingly, the cytotoxicity of the β-CD:EV inclusion complex was remarkably improved when combined with FGF7, P < 0.001 (Figure 10) with a dramatic decrease in the IC 50 value from 17.71 ± 1.42 to 1.87 ± 0.33 μM. Hence, FGF7 facilitated the intracellular delivery of EV.…”
Section: Discussionmentioning
confidence: 96%
“…The IC 50 value of β-CD:EV was higher than that of EV, suggesting that conjugation significantly affect EV efficacy ( P < 0.01), possibly due to the slow release profile of EV from the inclusion complex. 47,48 Interestingly, the cytotoxicity of the β-CD:EV inclusion complex was remarkably improved when combined with FGF7, P < 0.001 (Figure 10) with a dramatic decrease in the IC 50 value from 17.71 ± 1.42 to 1.87 ± 0.33 μM. Hence, FGF7 facilitated the intracellular delivery of EV.…”
Section: Discussionmentioning
confidence: 96%
“…Paclitaxel loaded cyclodextrin nanospheres play an important role of the anticancer activity in 3D multicellular spheroids MCF-7 and following on drug delivery system was investigated in vivo studies as described previously. 53 Previous reports were indicated that expression of CXCR 4 in the cancer cells was enhanced. 54 Curcumin-loaded CS-ALG-TPP NPs strongly decreased the apoptotic gene expression ( Bax ) and also significantly decreased the anti-apoptotic gene expression ( Bcl2 ) compared with carrier and free curcumin.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, their dense hydroxyl display can be selectively functionalized to render an array of amphiphilic structures featuring spontaneous self-assembling capabilities in an aqueous environment, whose functional properties (i.e., stability, encapsulation capabilities, surface, interaction abilities, or environmental sensitivity) can be tailored. In fact, these nanodelivery systems were applied for the delivery of various anticancer drugs such as PCX [ 13 , 14 , 15 ], erlotinib [ 16 ], camptothecin [ 17 , 18 , 19 ], docetaxel [ 20 ], genistein [ 21 ], sorafenib [ 22 ], and quercetin/silibinin [ 23 ]. In addition, it has been preferred in studies to increase the effectiveness of various molecules besides anti-cancer drugs in different strategies such as gene silencing or phototherapy in cancer treatment [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, two different amphiphilic βCDs were used in the study. Non-ionic 6OCaproβCD and cationic PC βCDC6 were used in our previous studies to create nano-sized carrier systems for anti-cancer drugs through oral or parenteral administration routes [ 13 , 15 , 16 , 17 , 19 , 31 ]. Our formulation development studies revealed both CDs as optimal carriers for PCX in our previous studies through cell culture studies and detailed in vitro characterization data including particle size, drug-loading efficiency, drug release profile, stability, hemolysis, and cytotoxicity in healthy cells [ 15 , 31 ].…”
Section: Introductionmentioning
confidence: 99%